Combination of cyclosporine A and methylprednisolone to treat pediatric Stevens-Johnson syndrome/toxic epidermal necrolysis overlap syndrome - Shinta Trilaksmi Dewi; Laily Noor Qomariah; Widya Khairunisa Sarkowi; Monika Puspitasari; Miya Khalidah; Marcella Anggatama; Dwinanda Almira Rizkiani; Kristiana Etnawati; Sri Awalia Febriana (PAGEPress Publications, 2023)
The treatment of epidermal necrolysis in pediatric patients remains a major challenge. Cyclosporine A has emerged as a promising therapy for epidermal necrolysis in adults; however, its efficacy in children is unclear. We present the case of a boy with Stevens-Johnson syndrome/toxic epidermal necrolysis overlap syndrome who was initially resistant to methylprednisolone monotherapy but improved after receiving the combination of cyclosporine A and methylprednisolone. Published reports on the use of cyclosporine A for pediatric epidermal necrolysis are also briefly reviewed.